A review on medicine in medieval times and the multicultural origin and development of the Salerno Medical School - Ha, Sha (Medicina Historica, 2022)
The Islamic medical knowledge had a threefold origin: the classical Greek and Roman teaching of Hippocrates, Dioscorides and Galen (whose works were saved in the Byzantine libraries of the conquered territories of Egypt and the Near East), the studies by Persian scholars from the Sasanian ‘Academy of Gondishapur’ and the ‘Ayurveda’ precepts of the sacred Sanskrit texts contained in temples of the Hindus Valley. All those works had been translated into Arabic in Baghdad’s ‘House of Wisdom, a great library founded by the Abbasid Caliph al-Mamun in 825 A.D.: those texts were later re-translated into Latin and hand-copied by Benedictine monks in the ‘scriptoria’ of Monte Cassino and other monasteries of Western Europe. The Great Mosque of Uqba, in Kairouan (North Africa) and the Great Mosque of Cordoba (in the Iberian Peninsula) were cultural centers where scientific and philosophical studies flourished and important medical works were produced. The scholars from the ‘Salerno Medical School’, established by Benedictine monks in that Southern Italian city state in 851 A.D., studied those works and contributed to the advancement of medical knowledge in Western Europe. The Chinese knowledge of herbal medicine was indirectly part of these cultural exchanges, following the Arab expansion in Transoxania in the 8th century A.D. What has emerged in more recent times is the contribution by female scholars and medical practitioners to the advancement of medical science in Western Europe during medieval times.